Enhancing Arabic Language Proficiency through Interactive Learning Programs - Lazuardi, Achmad Makki; Syarif Muhammad Syaheed (Program Studi Pendidikan Bahasa Arab, 2025)
This study examines the effectiveness of interactive learning programs in enhancing Arabic language proficiency among intermediate-level students at Pondok Pesantren Darullughah Wadda’wah, Indonesia. This study employed a mixed-methods design, integrating both descriptive statistics and thematic analysis to provide comprehensive insights. Grounded in constructivist pedagogy and employing a mixed-methods approach, the research integrates quantitative data from pre- and post-test assessments with qualitative insights derived from classroom observations, teacher interviews, and student surveys. Interactive strategies—including role-plays, peer collaboration, muhawarah simulations, and gamified digital tools—were implemented to foster active engagement and contextual language use. Quantitative findings revealed statistically significant improvements across all language domains, with the most substantial gains observed in speaking fluency (+22.4 points) and reading comprehension (+20.4 points). Qualitative data further illustrated a marked shift in student behavior, from passive reception to confident participation, as well as reductions in language anxiety and heightened motivation. The use of digital media enhanced learner autonomy and vocabulary retention, while also supporting the development of a stronger linguistic identity among students. Despite challenges related to classroom management and teacher readiness, the study underscores the transformative potential of interactive, technology-enhanced, and culturally grounded pedagogy in Islamic boarding schools. The results offer practical implications for Arabic language curriculum design, teacher training, and policy reform, while also contributing to the broader discourse on learner-centered education in non-native Arabic-speaking contexts.